Self-powered nanodevices for fast UV detection and energy harvesting using core-shell nanowire geometry. (September 2018) - Lin, Chun-Ho; Fu, Hui-Chun; Lien, Der-Hsien; Hsu, Chia-Yang; He, Jr-Hau
Abstract: Developing multiple functionalities in nanodevices is a desirable objective in current nanotechnology, where the self-powered capability is one of the most demanded functions—without the need of external batteries, nanodevices can be operated independently and maintenance-free for a long period of time. In this study, we fabricated the core-shell nanostructured device employing multi-walled carbon nanotubes (CNTs) as inner cores and ZnO as outer shells, and demonstrate their multiple functionalities of fast UV detection and self-powered capability. The device features high photoconductive gain of 800 and short response time of 0.48 ms in air and 29 ms in vacuum. For energy harvesting, the device shows photovoltaic (PV) capability to drive a conventional liquid crystal display (LCD) with a V oc of 0.85 V and I sc of 5 nA. Those features demonstrate that our CNT-ZnO core-shell nanostructured device, performing both high photoresponsivity and PV capability, can be operated in different functionalities with or without external bias. Graphical abstract: fx1 Highlights: Multifunctional and self-powered carbon nanotube-ZnO core-shell nanostructured device. Fast photodetection with response time of 0.48 ms and high photoconductivity gain of 800. Photovoltaic capability to drive a conventional liquid crystal display with a Voc of 0.85 V and Isc of 5 nA.